CITTÀ D'EUROPA E CULTURA URBANISTICA NEL MEZZOGIORNO BORBONICO: Il patrimonio iconografico della raccolta Palatina nella Biblioteca Nazionale di Napoli - Raffaele Ruggiero (UrbsHistoriaeImago: Storia e immagine dei territori, dei centri urbani e delle architetture, 2018)
After centuries of submission to the foreign rulers, between the eighteenth and the nineteenth century the South of Italy took a leading role in the European political landscape, on one hand absorbing in its culture the huge heritage of values and knowledge of those civilizations, on the other hand appealing to its own scientists, intellectuals and technicians' fervid minds to achieve relevant international goals in the field of the public and urbanistic works. Kings, such as Charles of Bourbon and Ferdinand II, were the main promoters of this ransom and of the achieved primacies. Rummaging through the iconographic documents passed on their desks, nowadays rearranged in the Neapolitan National library Palatine collection and consulting the volumes of the Royal library, it turns out a great turmoil of ideas and projects, but also the confirmation of the large amount of potentialities unfortunately not completely expressed by the Neapolitan State: it occurred, it should be said, not only as a consequence of the end of the kingdom, but also as a result of the specific political responsibility of that dynasty: Unfortunately Italy's unification didn't enhance the heritage of these experiences, nor it rectified the structural inadequacies of the former regime; on the contrary the new State often contributed to increase them, stifling a socio-economic promise of development still today unrealized.